Tantangan dan Strategi Pengembangan Potensi diri Narapidana (Studi Kasus Lapas Kelas 1 Bandar Lampung) - Saputra, Irwansyah Ahmat; Monica, Dona Raisa; Tamza , Fristia Berdian (Indonesian Journal Publisher, 2025)
This study aims to identify the challenges and strategies in developing inmates' potential at Class 1 Correctional Facility in Bandar Lampung. Effective rehabilitation enables inmates to acquire skills and mental preparedness for reintegration into society. Using a qualitative case study approach, data were collected through interviews with inmates and correctional officers, analysis of rehabilitation program documents, and direct field observations. The findings reveal that major obstacles to inmates’ self-development include inadequate facilities, low individual motivation, social stigma, and a shortage of educators and mentors. However, several strategies have been implemented to address these challenges, including vocational training, character education, and spiritual guidance. The active role of correctional officers and collaboration with external organizations, such as NGOs and the private sector, also contribute to the success of rehabilitation programs. This study concludes that a holistic rehabilitation approach—encompassing technical skill development, psychosocial support, access to employment opportunities, and a strong mentoring system—can enhance rehabilitation effectiveness. Therefore, strengthening synergy between the government, society, and the business sector is crucial to ensuring the sustainability and long-term impact of inmate development programs.